Three problems of neo-Marxism, or What you need to know before using a neo-Marxist approach - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2021)
The maturity of the neo-Marxist approach in cognition is determined not only by the heuristics of its theoretical and methodological foundations, but also by self-critical reflection. Three initial problems of the neo-Marxist approach are identified, which are useful to take into account when using it in scientific research: excessive criticism of neo-Marxist cognition, ideological bias of the neo-Marxist approach, conceptual uncertainty of capitalism as an object of neo-Marxism. It is proved that the ideological component is falsely identified with all neo-Marxism, and the critical component is treated trivially. The problem of the neo-Marxist approach lies not in the fact of a negative judgment about the reality under study, but in the level of theoretical and methodological support for the critical approach. It is necessary to distinguish criticism as a negative judgment and criticism as a dialectical logic of negation. The researcher can avoid the critical and ideological component of neo-Marxist research within the framework of the scientific tradition of neo-Marxism. This tradition does not deprive the researcher of the possibility of scientific search for new socio-economic reasons for the transformation of capitalism or new political ones by the subject of anti-capitalist resistance. The difference is that the ideological goal setting orients the researcher to the construction of the revolutionary situation of capitalism, and the scientific one – to the knowledge of the revolutionary factors of the existing «capitalist construct». More complex problem of the neo-Marxist approach is the conceptual uncertainty of capitalism. This problem requires a solution at the level of the community of neo-Marxist theorists. The unresolved nature of this problem affects the initial positions of new neo-Marxist studies. It does not allow us to define capitalism as an object of neo-Marxist research of any subject orientation. There are two options for a research strategy in this situation. First, it is possible, based on the conventional concept of truth, to join some neo-Marxist definition of modern capitalism and implement one’s subject research within the framework of the tradition of a particular neo-Marxist theorist. Secondly, it is possible to use the hypothetical-deductive method and proceed from the chosen understanding of capitalism as a hypothetical position, where the author’s subject of research is constituted as a consequence of this hypothesis and requires a verification check for truth. The solvability of general neo-Marxist epistemological problems means that there are no obstacles to the widespread application of neo-Marxism in social cognition.